The Religiousness Of Pious Women In The Novel “Bidadari Bumi: 9 Kisah Wanita Salehah” By Halimah Alaydrus - Yulianti, Iin; Elpandari, Wanda Ayu; Muttaqien, Zaenal (AL-ADYAN, 2024)
Discussions about religious discourse (religiosity) in a literary work are currently quite interesting to discuss. This is related to literary works which are considered to be imaginary works of their authors so they do not have authority in discussing religious issues. Literary works seem to only be reading material that has recreational (entertainment) and aesthetic value. As is often found in literary works such as novels, poetry, short stories and pantuns. In fact, apart from the recreational and aesthetic function, literary works also have a moral function, meaning that literature also provides readers with knowledge about good or bad morals, thus literary works also have religious values (religiosity). One of them is a novel which contains many religious values. Novels can inspire readers to pay more attention to the religious side of life. This shows that the religious aspects contained in the novel are Islamic teachings. The novel Bidadari Bumi: 9 Stories of Salehah Women, is a novel that tells the story of a role model woman in Tarim, Hadramaut, Yemen. This novel is very worthy of being used as an example in life. Especially for Muslim women in this century who are experiencing a crisis of religious values, examples and role models for pious women. The novel Bidadari Bumi: 9 Stories of Salehah Women, is not just a reading novel, this novel is full of examples about life, and also the writing in this novel is presented in very good language, and is easy to understand. So it becomes a special attraction for readers.